Making an impact in healthcare contexts: insights from a mixed-methods study of professional misconduct. Issue 4 (4th July 2021) - Searle, R.H.; Rice, C.
ABSTRACT: The scarcity of public sector healthcare resources and the vulnerability of service users make the conduct of health professionals critically important. Health regulators, in delivering their core objective of patient protection, use empirical evidence to identify professionals' misconduct, improve their understanding of why misconduct occurs, and to maximize the effectiveness of regulatory actions that safeguard public trust in the healthcare system. This paper outlines the contribution of comparative academic analysis of three professions in the UK (doctors, nurses & midwives, and allied health professions) based on 6714 individual cases of professional misconduct. Three dynamic strands of ongoing impact are identified: "dialogue", that creates an international multi-stakeholder community of interest; "knowledge generation", which advances conceptual and empirical understanding of counterproductive work behaviour through sequential quantitative and qualitative study; and "dissemination", where practical learning is utilized by regulators, employers and other academics.